EFFECT OF GUIDED IMAGERY AND DEEP BREATHING ON PAIN REDUCTION DURING INTRAVENOUS CANNULATION AMONG HOSPITALIZED CHILDREN: A PRELIMINARY QUASI-EXPERIMENTAL STUDY - Irvan Nugroho, Tri; Sulistyowati, Priyatin; Dyah Puspasari, Fida (International Journal of Patient Safety and Quality, 2025)
BackgroundChildren undergoing intravenous cannulation often experience procedural pain that may cause distress and interfere with cooperation during treatment. This study aimed to examine the preliminary effects of guided imagery compared to deep breathing relaxation on pain reduction among hospitalized children undergoing intravenous cannulation.MethodsA quasi-experimental design with non-randomized control groups was conducted at Emanuel General Hospital Banjarnegara, Indonesia. Eight children aged 8–13 years participated, with four in the guided imagery group and four in the deep breathing group. Pain intensity was assessed using the Wong–Baker Faces Pain Rating Scale.ResultsThe guided imagery group demonstrated a mean pain score of 1.75 (SD = 0.50), significantly lower than the control group’s mean of 7.75 (SD = 1.71). Children receiving guided imagery showed calm facial expressions, minimal crying, and better procedural cooperation.ConclusionGuided imagery is a feasible, safe, and effective non-pharmacological technique for reducing procedural pain in hospitalized children. Future research with larger samples is recommended to confirm these findings.